Application of BIM Digital Information Technology in the Economic Optimization Operation of Integrated Energy Systems - Jingjing Bu (International Transactions on Electrical Energy Systems)
Energy is an important support for national economic development, and energy security directly affects national security, sustainable development, and social stability. The Middle East has the largest energy reserves in the world. Saudi Arabia is located in the Middle East and is a big energy country with very rich resources. With the reduction of fossil fuels and the increasingly prominent problem of climate change, the sustainable supply of energy while reducing environmental pollution and economic costs in the process of energy use is a problem facing the world today. In order to fully absorb clean energy, improve energy efficiency, and reduce fuel costs and environmental costs, we studied the impact of BIM digital information technology on the economic optimization of integrated energy systems. The integrated energy system has the characteristics of multienergy input and multienergy output. In terms of energy output, the system uses the principle of energy cascade utilization to recover and utilize the waste heat generated by the traditional generator set and then collects it through absorption. Compared with the traditional single-stage utilization of energy, the integrated energy system uses various forms of power, for example, power, heating, cooling, and natural gas, to achieve economic optimization by improving the comprehensive energy utilization efficiency through multienergy complementation. Through the investigation and comparison of the optimal dispatching operation cost, energy use cost, pollutant treatment cost, and equipment maintenance cost of 3 enterprises, the results show that the comprehensive energy system using BIM digital information technology can reduce the energy use cost by 8.7%. Moreover, the cost of pollutant treatment and the cost of equipment maintenance have been reduced to a certain extent, which has a certain optimization effect on the economy of comprehensive energy of enterprises.